Larval rearing of the spiny eel, Macrognathus aculeatus (Lacepede) under different rearing conditions: a preliminary study - Sahoo, S K; Giri, S S; Chandra, S; Sahu, A K (Indian Journal of Fisheries, 2011)
A study was carried out to evaluate the role of rearing conditions on growth and survival of the spiny eel, Macrognathus aculeatus (Lacepede) larvae during a 30 days experimental period. The study was conducted with three treatment groups: the first group was reared in fibre-glass tanks with 6" deep water (Treatment-1), the second group in tanks provided with floating weed covering one fourth of the water surface (Treatment-2) and the third group was reared in tanks provided with soil bed and floating weed (Treatment-3). The tanks used for treatments 1 and 2 were not provided with soil bed. The growth and survival rate of the larvae, reared in the tanks with normal bottom and weed as well as in normal bottom without weed did not differ (p<0.05). However, the growth and survival rate were significantly reduced (p<0.05) when reared in tanks with soil base as well as floating weed. The results indicated that either providing soil at tank bottom or weed in rearing system did not help increase growth and survival of this species during the experimental rearing.